1998
DOI: 10.1002/(sici)1096-8628(19980401)76:4<351::aid-ajmg12>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of supernumerary marker chromosomes in 38 patients

Abstract: We present cytogenetic and clinical data on 38 patients with supernumerary marker chromosomes (SMCs). SMCs were characterized using a strategy combining classical banding techniques and molecular cytogenetic studies. Cases were ascertained prenatally, postnatally, and after fetal death. In 26 patients (68%), the SMC originated entirely from acrocentric chromosomes. Among these, most patients carried a der(15). In 11 patients (29%), they were of nonacrocentric origin, including 9 autosomal and 2 gonosomal marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 35 publications
0
30
0
1
Order By: Relevance
“…Based on the comparison of clinical features of sSMC(18) carriers described earlier, we propose that tri-or tetrasomy of pericentromeric region of chromosome 18 results in tapering of fingers and motor developmental delay -features found also in patient MK (Viersbach et al 1998;Baumer et al 2002;Starke et al 2003;Guanciali-Franci et al 2004;Timur et al 2004;Bartsch et al 2005).…”
Section: Discussionmentioning
confidence: 75%
“…Based on the comparison of clinical features of sSMC(18) carriers described earlier, we propose that tri-or tetrasomy of pericentromeric region of chromosome 18 results in tapering of fingers and motor developmental delay -features found also in patient MK (Viersbach et al 1998;Baumer et al 2002;Starke et al 2003;Guanciali-Franci et al 2004;Timur et al 2004;Bartsch et al 2005).…”
Section: Discussionmentioning
confidence: 75%
“…It has been shown that de novo marker chromosomes are associated with an increased risk of mental retardation and/ or physical anomalies (1,5,11). Pre-natally ascertained cases of sSMC that have arisen de novo are particularly difficult to connect clinically to a phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The large variety of sSMCs, as well as the limitations in their cytogenetic identification, have presented a diagnostic problem in their interpretation. In general, the risk for an abnormal phenotype is approximately 13%, varying from 7% when de novo sSMCs derived from chromosomes 13, 14, 21 and 22 are encountered, to 28% for non-acrocentric (5). Studies of the cytogenetic and phenotypic effects of sSMCs gained a fresh impetus when fluorescence in situ hybridization (FISH) was utilized to identify their chromosomal origin (6).…”
Section: Introductionmentioning
confidence: 99%
“…The girl reported by Silahtaroglu et al (1995) was mentally retarded and had impaired speech and moderate dysmorphic facial features. A low-level mosaicism with a small extra ring X chromosome was found in a phenotypically normal girl (case 37, Viersbach et al 1998). Neither of these patients have features consistent with HI, but neither XIST status nor X-inactivation studies were carried out.…”
Section: Discussionmentioning
confidence: 94%